Pelatihan dan Penguatan Persiapan Kegiatan Olimpiade Matematika Dalam Penguatan Kemampuan Berfikir Pada Ekstrakurikuler Matematika Di Sma Negeri 1 Deli Tua - Siregar, Fransisco Dinata; Simbolon, Iwan Martua; Sianipar, Tabitha Gabriela; ., Kairuddin (Peneliti.net, 2026)
This study aims to describe the implementation of training and preparatory activities for the Mathematics Olympiad as an effort to enhance students’ logical and systematic thinking through extracurricular activities at SMA Negeri 1 Deli Tua. The training was carried out using diagnostic teaching and intensive problem-solving drills, supported by inquiry-based learning strategies. Conducted over three days, the program involved 30 students selected based on prior performance and interest in mathematics. Results indicate a significant improvement in students’ average scores, rising from an initial 36.5 to approach the Minimum Mastery Criteria (KKM) of 75. Additionally, 80% of participants reported increased confidence and readiness to face mathematical competitions. The findings suggest that structured extracurricular mathematics programs play a vital role in fostering critical thinking skills and preparing students for high-level academic challenges such as the Mathematics Olympiad.